Acetonitril [MAK Value Documentation in German language, 2018]. Issue 2 (24th April 2018) - Hartwig, A.; ,
Abstract: Acetonitrile causes an increased incidence of liver adenomas and carcinomas in rats at 400 ml/m 3 with a statistically significant trend. The number of basophilic foci in the liver is positively correlated with the exposure concentration. At 100 ml/m 3 the elevation is not statistically significant, however, these foci are regarded as preneoplastic lesions. From this concentration the former MAK value of 20 ml/m 3 was derived. It is now lowered to 10 ml/m 3 taking into account the increased respiratory volume at the workplace because the blood:air partition coefficient of acetonitrile is > 5 (see List of MAK and BAT values, chapters I b and I c). Since a systemic effect is critical, Peak Limitation Category II is retained. As the effects are probably due to the metabolites, the default excursion factor of 2 is confirmed despite the long half‐life of acetonitrile. For rabbits, the NOAEL for developmental toxicity after gavage is 15 mg/kg body weight and day. After toxicokinetic scaling this dose corresponds to a concentration of 34 ml/m 3 at the workplace. Rabbits are more sensitive to acetonitrile than rats and humans and the developmental toxicity of acetonitrile is higher after gavage than after inhalation exposure as shown with rats. Therefore, the rabbit gavage data are not used to assign a Pregnancy Risk Group. The NOAEC for developmental toxicity in rats is 1600 ml/m 3 and after considering the increased respiratory volume at the workplace the difference to the MAK value is sufficient. Therefore, damage to the embryo or foetus is unlikely when the MAK value is observed and acetonitrile remains assigned to Pregnancy Risk Group C.